Description of Preceptor Perceptions about Nursing Clinical Practice Performance Evaluation Instrument in Preceptorship Method - Tri Ismu Pujiyanto; Achmad Syaifudin (Humanistic Network for Science and Technology (HNST), 2019)
Learning experience in the form of clinical practice is an opportunity for students to apply all theories obtained both in the classroom and in the laboratory into a real setting, namely the field of practice in the hospital. Evaluation of nursing clinic practices is carried out to ensure the performance of students during practice in accordance with the expected competencies. The understanding of the Preceptors on the evaluation instrument of Nursing Clinical Practices is still varied, the components in the evaluation instrument are still incomplete, and subjectivity is still high. The aim of the research to find out the understanding and perception of the preseptor about the evaluation instrument for clinical practice of the preseptorship method. The method used in the initial stage is Quantitative research with survey design. The sampling technique was total sampling. The samples size were 20 clinical Nurses Preseptor from RSUD (hospital) “Ambarawa”. The results of the study showed that the majority of respondents understood and mastered how to fill the evaluation instrument for clinical practice in the preseptorship method. . Keywords: Clinical practice performance instrument, Nursing clinical practice, Preceptor